Differential Neuroplastic Changes in Fibromyalgia and Depression Indexed by Up-Regulation of Motor Cortex Inhibition and Disinhibition of the Descending Pain System: An Exploratory Study - Cardinal, Tiago Madeira; Antunes, Luciana Conceição; Brietzke, Aline Patricia; Parizotti, Cristiane Schulz; Carvalho, Fabiana; De Souza, Andressa; da Silva Torres, Iraci Lucena; Fregni, Felipe; Caumo, Wolnei (Frontiers in Human Neuroscience, 2019)
Background: Major depressive disorder (MDD) and fibromyalgia (FM) present overlapped symptoms. Although the connection between these two disorders has not been elucidated yet, the disruption of neuroplastic processes that mediate the equilibrium in the inhibitory systems stands out as a possible mechanism. Thus, the purpose of this cross-sectional exploratory study was: i) to compare the motor cortex inhibition indexed by transcranial magnetic stimulation (TMS) measures [short intracortical inhibition (SICI) and intracortical facilitation (ICF)], as well as the function of descending pain modulatory systems (DPMS) among FM, MDD, and healthy subjects (HS); ii) to compare SICI, ICF and the role of DPMS evaluated by the change on Numerical Pain Scale (NPS) during the conditioned pain modulation test (CPM-test) between FM and MDD considering the BDNF-adjusted index; iii) to assess the relationship between the role of DPMS and the BDNF-adjusted index, despite clinical diagnosis. Patients and methods: A cohort of 63 women, aged 18 to 75 years [FM (n=18), MDD (n=19) and HC (n=29)]. Results: The MANCOVA analysis revealed that the mean of SICI was 53.40% larger in FM compared to MDD [1.03 (0.50) vs. 0.55(0.43)] and 66.99% larger compared to HC [1.03 (0.50) vs. 0.34 (0.19), respectively. The inhibitory potency of the DPMS assessed by the change on the NPS during CPM-test was 112.29 % lower in the FM compared to MDD [0.22 (1.37) vs. - 0.87 (1.49)]. The mean of BDNF from FM compared to MDD was 35.70% higher [49.82 (16.31) vs. 14.12 (8.86)]. In FM, the Spearman`s coefficient between the change in the NPS during CPM-test with the SICI was Rho=-0.49, [confidence interval (CI) 95%; -0.78 to -0.03)]. The BDNF-adjusted index was positively correlated with the disinhibition of the DPMS. Conclusion: These findings support the hypothesis that in FM a deteriorated function of cortical inhibition, indexed by a higher SICI parameter, a lower function of the DPMS, together with a higher level of BDNF indicate that FM has different pathological substrates from depression. They suggest that an up-regulation phenomenon of intracortical inhibitory networks associated with a disruption of the DPMS function occurs in FM.